2020
DOI: 10.1386/atr_00027_1
|View full text |Cite
|
Sign up to set email alerts
|

‘Breath, Belief, Focus, Touch’: Applied puppetry in simulated role-play for person-centred nursing education

Abstract: As a subject area that sustains itself on the productive tension between human and non-human agency, applied puppetry is a pragmatic and compelling approach to considering the role of objects in an anthropocentric world. In health care, mannequins play the role of simulated patients. Most often, they simply stand in for the body of the patient. However, this misses the potential that the materiality of these objects holds when considered through applied puppetry terms. This article examines examples of puppet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…[29][30][31] Few studies have proposed The analytical results of this study indicated that nursing students who virtually experienced the conditions of perioperative patients through VR blended learning showed increased levels of empathy, positive attitudes toward patient safety treatment, confidence in nursing care, and clinical skill performance. This result is consistent with the results of meta-analyses, which showed increased levels of empathy and positive attitudes toward patient safety managementnecessary competencies for patient-centered care-during simulation training 14,26,27 and better interpersonal skills and self-efficacy during role-play. 25 Furthermore, nursing students' virtual experience as perioperative patients showed a positive correlation with their clinical skill performance.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[29][30][31] Few studies have proposed The analytical results of this study indicated that nursing students who virtually experienced the conditions of perioperative patients through VR blended learning showed increased levels of empathy, positive attitudes toward patient safety treatment, confidence in nursing care, and clinical skill performance. This result is consistent with the results of meta-analyses, which showed increased levels of empathy and positive attitudes toward patient safety managementnecessary competencies for patient-centered care-during simulation training 14,26,27 and better interpersonal skills and self-efficacy during role-play. 25 Furthermore, nursing students' virtual experience as perioperative patients showed a positive correlation with their clinical skill performance.…”
Section: Discussionmentioning
confidence: 98%
“…In most previous studies, scenario-based role-plays were performed to help nursing students gain more experience and a better understanding of being a patient. 14,[25][26][27] However, nursing students' experience of being a patient was limited because of the burden of acting and disturbance halting role-play immersion. 28 Thus, this study developed a method that enabled nursing students to understand patients' experience in realistic situations, as well as their conditions and needs, instead of role-play training in which nursing students simply played the role of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation